Epistomaroides punctatus (Said, 1949) - a new alien foraminifera found at Akhziv - Rosh HaNikra, northern Israel, eastern Mediterranean Sea - ALMOGI-LABIN, A.; HYAMS-KAPHZAN, O. (Mediterranean Marine Science, 2012)
The alien benthic foraminifera Epistomaroides punctatus (Said) is reported for the first time from the northern part of the Israeli coast. Three living specimens were collected in April 2005, at the vermetid reefs of Akhziv - Rosh HaNikra. Epistomaroides punctatus has so far only been reported from the Indo-Pacific realm; thus, it is suggested to be a Lessepsian invader.